ANALISIS PERFORMA BOILER ALSTOM BERDASARKAN RASIO ANTARA BAHAN BAKAR DAN STEAM DI PT. INDO ACIDATAMA Tbk. - Arief Suryo Wibowo; Danar Susilo Wijayanto; Nugroho Agung Pambudi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
This research aim to Investigate Alstom boiler performance based on the ratio between fuel consumption and steam production. This reasearch uses quantitative descriptive method. The Population in this research is an Alstom boiler. The sample in this research is daily record data Alstom boiler during one year (February 2015 untill January 2016). Data obtained from the research, were analyzed and entered to the table and displayed in graphical form. There are two indicators in this research: ratio that was gotten from comparation between fuel consumtion and steam production and energetic efficiency of Alstom boiler. Based on the research result can be summed up that Alstom boiler in excellent performance, because the ratio shown 133,59 kg coal / ton of steam is lower than the company target 140 kg coal / of steam, and energetic analysis of Alstom boiler 83,29% was higher than the company target 80%.